Incidence and outcomes of hospitalization for community-acquired, ventilator-associated and non-ventilator hospital-acquired pneumonias in patients with type 2 diabetes mellitus in Spain - Lopez-de-Andres, Ana (BMJ Open Diabetes Res Care, 2020)
INTRODUCTION: To describe the incidence and compare in-hospital outcomes of community-acquired pneumonia (CAP), ventilator-associated pneumonia (VAP) and non-ventilator hospital-acquired pneumonia (NV-HAP) among patients with or without type 2 diabetes mellitus (T2DM) using propensity score matching. RESEARCH DESIGN AND METHODS: This was a retrospective observational epidemiological study using the 2016–2017 Spanish Hospital Discharge Records. RESULTS: Of 245 221 admissions, CAP was identified in 227 524 (27.67% with T2DM), VAP was identified in 2752 (18.31% with T2DM) and NV-HAP was identified in 14 945 (25.75% with T2DM). The incidence of pneumonia was higher among patients with T2DM (CAP: incidence rate ratio (IRR) 1.44, 95% CI 1.42 to 1.45; VAP: IRR 1.24, 95% CI 1.12 to 1.37 and NV-HAP: IRR 1.38, 95% CI 1.33 to 1.44). In-hospital mortality (IHM) for CAP was 12.74% in patients with T2DM and 14.16% in matched controls (p<0.001); in patients with VAP and NV-HAP, IHM was not significantly different between those with and without T2DM (43.65% vs 41.87%, p=0.567, and 29.02% vs 29.75%, p=0.484, respectively). Among patients with T2DM, older age and dialysis were factors associated with IHM for all types of pneumonia. In patients with VAP, the risk of IHM was higher in females (OR 1.95, 95% CI 1.28 to 2.96). CONCLUSION: The incidence rates of all types of pneumonia were higher in patients with T2DM. Higher mortality rates in patients with T2DM with any type of pneumonia were associated with older age, comorbidities and dialysis.